Implementation of the e-kinerja application program in assessment of attitude in employee performance system at the regional service agency of Gorontalo regency office - Srihandayani Suprapto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This research aims to determine the extent of the implementation of the E-performance Application Program in Attitude Assessment in the Performance System of Civil Servants at the Regional Personnel Agency Office of Gorontalo Regency. Attitude assessment on the employee performance system is something that must be carried out in an agency or company, this is done to find out whether the results of employee performance are increasing or decreasing. This type of research uses a qualitative research approach with a descriptive research approach. To obtain accurate data, the obtained data was tested for validity using Nvivo 11. The results based on research findings it can be concluded that the implementation of the e-performance application program is not good enough because it still has several problems, such as civil servants who do not understand how to operate e-performance applications, but the BKD has carried out socialization and training so that civil servants can easily fill out performance results.